Assay method validation of triamcinolone acetonide (TA) to support the investigation of TA-loaded nanoparticles - Rini Nastiti, Cr. Maria Ratna (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Theaim of this study was to develop the valid analytical method which used for the assay of triamcinolone acetonide (TA) in the investigation of TA loaded nanoparticle formulations. High Performance Liquid Chromatography(HPLC) method was applied in his study by using an Econosil column,C1810 m, 250x 4.6mm (Alltech Associates Inc, PA,USA )as the stationary phase. Themobile phase consisted of a composition of acetonitrile (ACN) and 20mM phosphate buffer solution (pH 4.2) in the proportion of 50:50 v/v. The HPLCassay of TA was validated for selectivity, linearity, precision, ecovery (accuracy),sensitivity and stability of TA during the assay. Results showed that the concentration of TA in the sample scan be determined against the standard in the concentration range of calibration curve. The system precision and level of recovery were considered to be acceptable, and the method was selective and sensitive.Key words:triamcinoloneacetonide,assay,validation